Kualitas Pelayanan Penyelenggaraan Diklat Keterampilan Kepelautan Medical Care Dan Medical First Aid - Sukur Sukur; Rachmat Tjahjanto; Srinita YM (Hengkara Majaya, 2021)
The purpose of this study was to determine the quality of the service in the delivery of training for marine skills for Medical Care and Medical First Aid at Barombong Maritime Polytechnic. The data analysis used was descriptive quantitative data analysis using the questionnaire method. Testing of the data in this study used variable validity and reliability tests. The results of this study indicate that the quality of services for maritime education and training, especially medical care and medical first aid, has been going well, thus from the above results it can be concluded that the indicators of Tangible, reliability, responsibility, assurance and empathy have gone well and must be improved so that training can improve service quality.